Attitude, Solidarity, and Social Change in Indonesian Presidential Debate 2019 - Chrisdianto Wibowo Kamandoko; Sukarno Sukarno; Ikwan Setiawan (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
The research aimed to identify the solidarity and social change represented by the presidents’ attitudes in the debates. The research applied positive discourse analysis purposed by Martin (2004) and the appraisal framework, especially the attitude system purposed by Martin and White (2005). The results showed that Prabowo used more attitudes in his argument than Jokowi. Prabowo tended to use more judgements and appreciations to show his attitudes. On the other hand, Jokowi preferred to use affect, which is desire and trust, to express his attitude. Solidarities were performed in their attitudes by means of concern toward audiences and by means of respect between appraisers. Thus solidarities are responsible for bringing social changes such as habits, behavior, mindset, value, and norms, and also in terms of the developments of technology and transportation.